Avaliação do emprego de sulfato de amônio, ácido cítrico e óxido de magnésio como aditivos na dissolução da cal, visando aplicações em processos de SDA para remoção de enxofre - Lima, Magno Luís Bezerra (2018)
After the wet scrubbing process, SDA (Spray Drying Absorption) is the most common technology used for FGD (Flue Gas Desulfurization) purposes. Even though they possess a lower energy demand, SDA systems have limited sulfur removal capacity compared to the conventional wet process. One way to overcome this issue is to improve the mass transfer in the liquid phase by adding a compound that increases the lime dissolution rate. Among several suitable compounds reported in the literature, magnesium oxide, citric acid and ammonium sulfate were found to be most attractive ones due to the their low cost. Therefore, the present study aims to investigate the utilization of citric acid, magnesium oxide and ammonium sulfate as additives in lime dissolution in order to enhance the performance of semi-dry FGD processes. The influence of the temperature and stirring speed were also evaluated. The experiments were carried out in a pH-stat apparatus and the dissolution rate was estimated on the basis of shrinking core model. The experimental data was analyzed by means of a regression model. Both the mass transfer and reaction process were found to have an important role in the system. Ammonium sulfate demonstrated the best results, increasing the dissolution rate by up to 100 %. On the other hand, the presence of citric acid improved the dissolution rate by only 15 % and a slower dissolution rate was obtained when magnesium oxide was added. Moreover, the effect of ammonium sulfate was found to be strongly affected by the temperature and stirring speed.